Slog's dad - Almond, David, 1951-; McKean, Dave (Somerville, Mass. : Candlewick Press, 2011)
Slog, having been told by his father before his death that he will come back and visit him, is convinced the man on the bench outside of the butcher shop is his dad, but his friend, Davie, has a hard time believing it is true.
Young Adult
Young Adult
Keywords: Death -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Future life -- Juvenile fiction; Death -- Fiction; Fathers and sons -- Fiction; Future life -- Fiction; Death -- Fiction; Father-son relationship -- Fiction; Future life -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction